Logic-based schedulability analysis for compositional hard real-time embedded systems - Pedro, André Matos (2015)
This is the author's version of the work. It is posted here by permission of ACM for your personal use. Not for redistribution. The definitive version was published in SIGBED Review, VOL.12, ISS.1, http://doi.acm.org/10.1145/2752801.2752808